2022
DOI: 10.5916/jamet.2022.46.3.128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of effect of coherent and incoherent components on RCS of chaff cloud

Abstract: the radar scattering characteristics ,f each source of return and in which parts of the antenna pattern t'ey may be found. Clutter signals are due to direct terra~in reflections that occur at the same effective range as the target, and multipath signals are due to indirect reflections from the terrain between the target and . . •

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…The EC and GEC are methods for calculating the electromagnetic characteristics of the entire scattering body by replacing the chaff cloud formed by the dispersion of the chaff fibers with an effective medium [21]. Especially, the GEC can be applied to chaff clouds with arbitrary orientation distributions.…”
Section: Generalized Equivalent Conductor (Gec) Methodsmentioning
confidence: 99%
“…The EC and GEC are methods for calculating the electromagnetic characteristics of the entire scattering body by replacing the chaff cloud formed by the dispersion of the chaff fibers with an effective medium [21]. Especially, the GEC can be applied to chaff clouds with arbitrary orientation distributions.…”
Section: Generalized Equivalent Conductor (Gec) Methodsmentioning
confidence: 99%
“…As a result, it can be concluded that minimizing the interval between bursts or dispensing multiple chaff simultaneously is more effective in creating a larger RCS before the fighter passes through the RRC. However, electromagnetic coupling and shielding of chaff limit the increase in RCS from dispensing chaff at very short intervals or multiple chaff bursts compared to a single chaff cartridge [7][8]. For this study, it is assumed that the chaff RCS remains constant regardless of the chaff dispense sequence.…”
Section: Methodology For Chaff Dispense Programmentioning
confidence: 99%